The Effect of a Collaborative Approach in Management of Chronic Diseases in the Elderly: Case Study at a Community Health Center - Rezeki Nur; Kruger Margarida; Woolnough Cale; Aria Pranatha (Yayasan Adra Karima Hubbi, 2024)
Chronic disease management in the elderly demands a holistic and collaborative approach to improve quality of life and reduce the risk of complications. Community Health Centers (Puskesmas) often act as the main service institutions for elderly people who require long-term care. This study aims to evaluate the impact of a collaborative approach to chronic disease management in the elderly in the Community Health Center environment. This research method uses a case study conducted at a community health centre involving elderly people with chronic diseases and the health care team. Data was collected through observation, interviews and analysis of medical records. The results of this study showed significant improvements in health monitoring, adherence to treatment, and understanding of disease conditions. Collaboration that occurs between healthcare teams in a coordinated manner helps optimize resource utilization and accelerate responses to changes in health conditions. The conclusions of this study emphasize the urgency of a collaborative approach to the management of chronic diseases in the elderly at Community Health Centers. Collaboration between seniors, families, and the health care team has a significant impact on improving quality of life and reducing the risk of complications. Further efforts need to be made to increase public understanding of the importance of collaborative roles in chronic disease management.